Advancements in smart city and intelligent building : proceedings of the International Conference on Smart City and Intelligent Building (ICSCIB 2018) /: proceedings of the International Conference on Smart City and Intelligent Building (ICSCIB 2018). (2019) - Unknown
No abstract available